Evaluation of Babesia Spp. Infection among Native Horses in Quezon Province, Philippines, Using Molecular and Microscopical Examination - Fletcher P.Del Valle; Abigail M.Baticados; Varen N.Baticados (The Iranian Journal of Veterinary Science and Technology, 2011)
The possible existence of equine piroplasmosis was investigated in the province of Quezon, Philippines. Blood samples of 269 horses from selected municipalities of Quezon Province were gathered. Parasitological test namely blood parasite examination was employed and the test yielded negative results for the presence of the parasite. Similarly, polymerase chain reaction assay was performed using Babesia genus-specific primers. PCR assay also resulted to all samples being negative for the disease. The negative results are suggestive of a variety of causes specifically; low parasite concentration during sample collection, localization of the parasite in the endothelium, latent stage of infection, acquired immunity, drug intervention and true negative or complete absence of parasite in the blood. The abovementioned reasons are either characterized by very low parasitemia, no parasitemia or eventually complete disappearance of the parasites in the blood, all of which subsequently confounds the observance of the parasite.